The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.neuropsychologia.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

The effects of healthy aging, amnestic mild cognitive impairment, and Alzheimer's disease on recollection, familiarity and false recognition, estimated by an associative process-dissociation recognition procedure

Abstract: a b s t r a c tGiven the uneven experimental results in the literature regarding whether or not familiarity declines with healthy aging and cognitive impairment, we compare four samples (healthy young people, healthy older people, older people with amnestic mild cognitive impairment -aMCI -, and older people with Alzheimer's disease -AD -) on an associative recognition task, which, following the logic of the processdissociation procedure, allowed us to obtain corrected estimates of recollection, familiarity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Our findings did not produce evidence that these meta-cognitive measures may be sensitive marker of preclinical and prodromal AD, as they did not show different longitudinal decline patterns according to the diagnostic groups and their stability or progression toward more advance stages of cognitive impairment. They are therefore consistent with the findings of a previous follow-up study (Facal et al, 2016a) although its methodology was not longitudinal (including only baseline and follow-up assessments) and results inform about mean differences between groups; but they contrast with the evidence provided in some cross-sectional studies (Wolk et al, 2013;Pitarque et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings did not produce evidence that these meta-cognitive measures may be sensitive marker of preclinical and prodromal AD, as they did not show different longitudinal decline patterns according to the diagnostic groups and their stability or progression toward more advance stages of cognitive impairment. They are therefore consistent with the findings of a previous follow-up study (Facal et al, 2016a) although its methodology was not longitudinal (including only baseline and follow-up assessments) and results inform about mean differences between groups; but they contrast with the evidence provided in some cross-sectional studies (Wolk et al, 2013;Pitarque et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Facal et al (2016a) also considers "familiarity" as a ToT measure of meta-cognitive processes involved in ToTs that indicate that the name knowledge is present (Schwartz and Metcalfe, 2011). Although some cross-sectional studies suggest that familiarity-based memory measures may be sensitive markers of preclinical and prodromal Alzheimer's Disease (AD, Wolk et al, 2013;Pitarque et al, 2016), the longitudinal approach did not show any evidence of their predictive value (Facal et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…There has been some conflicting results regarding the fate of familiarity in AD and its prodromal stage. Several studies reported impaired familiarity (Algarabel et al, 2012;Ally, Gold, & Budson, 2009;Besson et al, 2015;Gallo et al, 2004;Hudon, Belleville, & Gauthier, 2009 (in AD patients); Pitarque et al, 2016;Westerberg et al, 2013 (in AD patients); Wolk et al, 2011;Wolk, Mancuso, Kliot, Arnold, & Dickerson, 2013;Wolk, Signoff, & DeKosky, 2008), while others showed intact familiarity in the patients (Belleville, Ménard, & Lepage, 2011;Genon et al, 2013Genon et al, , 2014Hudon et al, 2009 (in MCI patients);Troyer et al, 2012;Wang, Yonelinas, & Ranganath, 2013;Westerberg et al, 2013 (in MCI patients)). Various reasons have been proposed to explain this variability in findings, including methodological differences (Koen & Yonelinas, 2014;Schoemaker et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These patients would have to mainly use an automatic information processing, given their well-known recollection deficits (Budson et al, 2002). Results such as those offered in the studies by Abe et al (2011), Gallo et al (2004), or Pitarque et al (2016) point in this direction, but further research is also needed along these lines.…”
Section: False Recognitionmentioning
confidence: 97%
“…“I remember that I studied items A, B, and C, but not item D, so I reject D”). Many studies have found support for the correct use of this recollection-based monitoring strategy in young people, but less in healthy older people or patients with cognitive impairment, due to their aforementioned item-specific deficits (Gallo, Sullivan, Daffner, Schacter, & Budson, 2004; Pitarque et al., 2016; Pitarque, Sales, Meléndez, & Algarabel, 2015).…”
Section: Introductionmentioning
confidence: 99%